2021
DOI: 10.1016/j.exer.2021.108535
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomics of the developing zebrafish lens and identification of putative controllers of lens development

Abstract: The vertebrate lens is a valuable model system for investigating the gene expression changes that coordinate tissue differentiation due to its inclusion of two spatially separated cell types, the outer epithelial cells and the deeper denucleated fiber cells that they support. Zebrafish are a useful model system for studying lens development given the organ's rapid development in the first several days of life in an accessible, transparent embryo. While we have strong foundational knowledge of the diverse lens … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 102 publications
4
30
0
Order By: Relevance
“…Crystallins, which constitute a substantial part of the refractive structure of the vertebrate eye lens and play a critical role in embryonic lens development, were downregulated in PTZF [63]. A single-cell transcriptome analysis study of ZF showed that crystallins (cryaa (crystallin, alpha A) and crybgx (crystallin beta-gamma X)) are exclusively expressed in lens fiber cells starting at 2 dpf [64]. In our study, the biological process linked with visual system development and perception was among the top GO terms (Figure 5), indicating that phosmet triggers ocular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Crystallins, which constitute a substantial part of the refractive structure of the vertebrate eye lens and play a critical role in embryonic lens development, were downregulated in PTZF [63]. A single-cell transcriptome analysis study of ZF showed that crystallins (cryaa (crystallin, alpha A) and crybgx (crystallin beta-gamma X)) are exclusively expressed in lens fiber cells starting at 2 dpf [64]. In our study, the biological process linked with visual system development and perception was among the top GO terms (Figure 5), indicating that phosmet triggers ocular toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In their more recent CRISPR lines there were no reported general larval defects, further suggesting that the morpholino-induced lens defects were not specifically due to the loss of aB-crystallin proteins. Existing data suggest that neither cryaba nor cryabb are significantly expressed in the zebrafish lens through 5 dpf, based on shotgun proteomics (Greiling, Houck & Clark, 2009) and single cell RNA-Seq (Farnsworth, Posner & Miller, 2021). These previous findings might explain the lack of noticeable early lens phenotypes in our aB-crystallin homozygous null larvae.…”
Section: Discussionmentioning
confidence: 66%
“…This allowed us to determine if mutation led to a decrease in mRNA levels for the damaged gene or changes in expression of the other α-crystallin genes. Whole larvae were assessed at 7 dpf as earlier work showed low levels of cryaba and cryabb expression through 4 and 5 dpf, respectively (Posner et al, 2017), and almost no expression in the lens (Farnsworth, Posner & Miller, 2021). We found reduced levels of cryaa mRNA in 7 dpf homozygous null mutants with the large deletion removing the proximal promoter and start codon (Fig 7A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations